2020
DOI: 10.1021/acssynbio.0c00326
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Complex DNA Rearrangements during Early Stages of HAC Formation

Abstract: Human artificial chromosomes (HACs) are important tools for epigenetic engineering, for measuring chromosome instability (CIN), and for possible gene therapy. However, their use in the latter is potentially limited because the input HAC-seeding DNA can undergo an unpredictable series of rearrangements during HAC formation. As a result, after transfection and HAC formation, each cell clone contains a HAC with a unique structure that cannot be precisely predicted from the structure of the HAC-seeding DNA. Althou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…4). This is important because earlier generations of HACs typically formed in a manner accompanied by large-scale DNA sequence multimerization and even acquisition of portions (>100 kb) of host cell chromosomal DNA ( 16 , 37 , 38 ). YAC- Mm -4q21 LacO contains a single Fse I site (fig.…”
Section: Yac-mm-4q21laco Hacs Harbor Multidomain Centromeres For Fait...mentioning
confidence: 99%
“…4). This is important because earlier generations of HACs typically formed in a manner accompanied by large-scale DNA sequence multimerization and even acquisition of portions (>100 kb) of host cell chromosomal DNA ( 16 , 37 , 38 ). YAC- Mm -4q21 LacO contains a single Fse I site (fig.…”
Section: Yac-mm-4q21laco Hacs Harbor Multidomain Centromeres For Fait...mentioning
confidence: 99%
“…Using transformation-associated recombination in yeast, it was shown that 2mer or 4mer or 5mer alphoid DNA repeats consisting of alphoid 170 bp monomers and having the ends homologous to each other may be one-step TAR-assembled into long synthetic alphoid DNA arrays varying in size from 50 to 140 kb (Step 1: Figure 11 ). After transfection of such arrays into human cells, de novo HACs are generated, ranging in size from 1 to 10 Mb due to amplification of the input alphoid DNA arrays (Steps 2 and 3) [ 139 143 ]. Because any nucleotide in the original dimer can be easily changed before its amplification, this TAR-based method allows to identify the critical regions of the alphoid repeat for de novo centromere seeding.…”
Section: Applications Of Tar Cloningmentioning
confidence: 99%
“…In nature, DNA concatenation could be used by viruses to amplify genome copy numbers [ 1 , 2 ]. Alternative applications of this principle include mitochondrial DNA replication [ 3 ], telomere maintenance [ 4 ], and multimerization of human artificial chromosomes [ 5 ] or replicative plasmids [ 6 ]. We will use the term “concatenation” in the context of transgene delivery, when tandemly arrayed transgene copies co-integrated into a genomic site.…”
Section: Historical Overview Of the Concatenation Studiesmentioning
confidence: 99%
“…One model predicts that a concatemer is built from one or more circular copies through de novo amplification by a rolling circle amplification or other means. This model could be inferred from the high efficiency of concatenation, the notion of occasionally observed identical transgene-transgene junctions [ 31 ], and the fact that cells possess mechanisms for gene amplification [ 5 , 32 , 33 ]. However, the amplification hypothesis was disproved by the studies with concatenation reporters, which demonstrated that copies in the concatemers are unique ( Figure 1 B–D) (see below).…”
Section: Historical Overview Of the Concatenation Studiesmentioning
confidence: 99%